PELABELAN TOTAL SISI AJAIB SUPER (TSAS) PADA GABUNGAN GRAF BINTANG GANDA DAN LINTASAN - Sudarsana, I Wayan; Noviana, Noviana; Musdalifah, Selvy; Kasim, Anita Ahmad (Univ. Tadulako, 2013)
An edge-magic total (EMT) labeling on a graph G(V,E) with the vertex set V and the edge set E, where |V| = p and |E| = q, is a bijective function ?: V E 1, 2, 3, ..., p + q with the property that for each edge (xy) of G, ?(x) + ?(xy) + ?(y) = k, for a fixed positive integer k. The labeling ? is called a super edge magic total (SEMT) if it has the property that for each vertex obtain the smallest label, (V) = 1, 2, ..., p. A graph G(V,E) is called EMT (SEMT) if there exists an EMT (SEMT) labeling on G. Study on SEMT labeling for the union of stars and paths initiated by Figueroa-Centeno et al. [2] with graph form . Furthermore, an investigation will be conducted on SEMT labeling of double stars and path, that are 2 ; 2 ; 2 and 2 . We obtain that the graphs presented above are SEMT with the magic constants k = , , and , respectively